2016
DOI: 10.1016/j.neubiorev.2016.07.021
|View full text |Cite
|
Sign up to set email alerts
|

Electronic communication based interventions for hazardous young drinkers: A systematic review

Abstract: Please cite this article as: O'Rourke, L., Humphris, G., Baldacchino, A., Electronic communication based interventions for hazardous young drinkers: A systematic review.Neuroscience and Biobehavioral Reviews http://dx.doi.org/10. 1016/j.neubiorev.2016.07.021 This is a PDF file of an unedited manuscript that has been accepted for publication. As a service to our customers we are providing this early version of the manuscript. The manuscript will undergo copyediting, typesetting, and review of the resulting p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
21
0
3

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 133 publications
0
21
0
3
Order By: Relevance
“…Further, there is inconclusive evidence on the optimal dose of mobile interventions to obtain the best effects (Berman, Gajecki, Sinadinovic, & Andersson, 2016). Having said that, one previous review suggested that the length of interventions did not have an impact on effectiveness (O'Rourke, Humphris, & Baldacchino, 2016). Also, it should be noted that while there are now hundreds of commercial alcohol-related smartphone apps available on the iTunes and Google Play stores, less than 20% of apps promote alcohol reduction (Milward et al, 2016), and very few of these contain valid behavioural change techniques (Crane, Garnett, Brown, West, & Michie, 2015).…”
Section: Individual Interventions (Iv): Digital Interventionsmentioning
confidence: 99%
“…Further, there is inconclusive evidence on the optimal dose of mobile interventions to obtain the best effects (Berman, Gajecki, Sinadinovic, & Andersson, 2016). Having said that, one previous review suggested that the length of interventions did not have an impact on effectiveness (O'Rourke, Humphris, & Baldacchino, 2016). Also, it should be noted that while there are now hundreds of commercial alcohol-related smartphone apps available on the iTunes and Google Play stores, less than 20% of apps promote alcohol reduction (Milward et al, 2016), and very few of these contain valid behavioural change techniques (Crane, Garnett, Brown, West, & Michie, 2015).…”
Section: Individual Interventions (Iv): Digital Interventionsmentioning
confidence: 99%
“…The ability to set own drinking goals is also highly valued [15]. Similarly, in the broader mobile health (mhealth) literature beyond apps alone, comparable conclusions are also drawn; for example, text message based interventions have demonstrated effectiveness in both decreasing intentions to consume alcohol and in actual drinking behaviour [16, 17], with this type of intervention liked by users on the basis of ease and convenience [18]. Other forms of digital intervention, including email, additionally seem to be accepted by recipients, primarily given their scope to tailor and personalise content [16], but may elicit lower levels of actual engagement compared to similar information and BCTs delivered via mobile phone [19].…”
Section: Introductionmentioning
confidence: 99%
“…In Switzerland, 17% of the population and 41% of young adults ages 20-24 years exhibit at least problematic alcohol use (Gmel, Kuendig, Notari, & Gmel, 2016), and heavy drinking remains the leading cause of mortality and morbidity in adolescence and early adulthood (Marmet, Rehm, Gmel, Frick, & Gmel, 2014). Technology-based alcohol interventions have been shown to be efficacious at reducing short-term risky alcohol use and alcohol-related problems in adolescents (O'Rourke, Humphris, & Baldacchino, 2016;Patton et al, 2014), but reviews also underline the unknown generalizability of current findings, since most studies have been conducted on student populations (Danielsson, Eriksson, & Allebeck, 2014;Donoghue, Patton, Phillips, Deluca, & Drummond, 2014;White et al, 2010).…”
Section: Introductionmentioning
confidence: 99%